STATES PHILOSOPHY ISLAM OR PANCASILA: THE POLITICAL ATTITUDES OF NAHDLATUL ULAMA PARTY IN THE CONSTITUANT ASSEMBLY - Muhammad Ilham Gilang (Candrasangkala: Jurnal Pendidikan dan Sejarah, 2018)
This paper discusses the role of the Nahdlatul Ulama Party during the national religious, social and political stage during the Liberal Democracy era. The NU party plays a political role in the Constituent Assembly. PNU, through its faction, proposed the Pancasila-Islam formulation as an effort to bridge the conflict between the 'Pancasila Block' and the 'Islamic Block', and recommended the main questions that must be contained in the new constitution. Then, NU's political attitude towards Nasakom was accommodative and persuasive towards Soekarno as the owner of Nasakom's idea. The emergence of these two political attitudes rests on religious views, namely amar ma'ruf nahi munkar (advocating good and preventing evil) and the ushul fiqh principle "Dar'ul mafasid muqaddamun 'alaa jalb al-mashalih" (avoiding danger is prioritized by doing good. ) as a basis for thinking, acting, and behaving in politics.